Questioning the Existence of The Indonesian Commision State : An Idea of Reconstruction - Antari, Putu Eva Ditayani (International Journal of Law Reconstruction, 2021)
This research focuses on the phenomenon of the large number of state commissions in Indonesia, especially in the post-reform era. The purpose of this study is to describe the classification of state commissions in Indonesia. Furthermore, through the idea of simplifying the state commission, it will be able to overcome the problems that often occur due to the large number of state commissions. Through doctrinal legal research using a conceptual and comparative approach, it is known that state commissions are formed as a form of democracy, where there are independent institutions with the main task of supervising the three axes of state power (trias politica), especially in the sphere of government power. This state commission has a legal basis for the formation of various institutions through laws, government regulations, or presidential regulations so that not all state commissions have an equal position in the state administration. Furthermore, the incidental and responsive nature of the formation of state commissions often results in overlapping powers of state commissions. In order to resolve this, the idea is to make simplifications for the current State commission. The act of simplification is carried out by only maintaining a few State commissions that are capable of supporting the spirit of democracy in the State. Meanwhile, other commissions were merged into institutions of other countries. Furthermore, it is given legitimacy based on law to the State commission, so that it is not difficult to determine its position in the Indonesian constitutional systemÂ Â